Artificial Intelligence Techniques In Enhancing the effectiveness of internal control procedures (World Economics and Finance Bulletin, 2025)
The research aims to identify the concepts and techniques of artificial intelligence, determine the nature and concept of internal control system procedures, and explain the role of artificial intelligence techniques in improving the effectiveness of internal control procedures. The research reached a set of conclusions, the most important of which is that increasing knowledge and learning about artificial intelligence techniques and employing these techniques to improve internal control activity is of great importance to decision-makers, and that the existence of a set of rules for using artificial intelligence techniques is considered a guiding model that achieves the guarantee and security of exploiting artificial intelligence applications, in addition to the fact that the processes of retrieving information and data from the database, analyzing and archiving them electronically greatly assist in decision-making processes. The research recommended the importance of providing electronic learning and training programs to keep pace with modern technologies in the work environment and the necessity of using the latest programs to use artificial intelligence techniques within internal control activities due to its importance in reducing time and effort.
Keywords: Artificial Intelligence; Internal Control Procedures; Effectiveness